Acceptability of artificial insemination by donor among infertile women attending the Gynaecological Clinic of the University College Hospital, Ibadan (2017)
Background: Artificial insemination by donor (AID) is specifically indicated in cases of incurable male infertility. Acceptability depends on perceptions largely influenced by religious and sociocultural perspectives. Male factor accounts for 20-50% of the causes of infertility and shows geographic variation in Nigeria. Method: A descriptive cross-sectional survey of all infertile women attending the gynecology clinic of the University College Hospital, Ibadan, between January and June 2014. 181 self-administered questionnaires were distributed to all consenting infertile women, however only 163 were suitable for analysis. Data analysis was descriptive and inferential at 95% confidence interval and a P value of less than 0.05 was considered statistically significant. Result: The mean duration of infertility was 5.7 ± 4.33 years. Fifty seven (35.0%) respondents were willing to accept artificial insemination by donor, while ninety three (57.1%) were unwilling to accept artificial insemination. Socio-cultural factor (48.1%) was the major reason for non-acceptability of artificial insemination by donor. Acceptability of AID was influenced by adequate knowledge about the procedure (P < 0.01). Sixty percent of the respondents had good knowledge and over half of them obtained the information from the news/print media. In this Study, acceptability of AID was not influenced by the age of the respondents, family structure, duration or type of infertility or educational status. (P > 0.05). Conclusion: This study revealed a low acceptance rate for Artificial insemination by donor. Providing information on AID as a treatment option during counseling and routine infertility management may be the needed drive to improve awareness and promote uptake when necessary.